Investigating the Relationship between Foreign Language Anxiety and Oral Performance of Non-English Major University Students in Indonesia - Subekti, Adaninggar Septi (Dinamika Ilmu: Jurnal Pendidikan, 2018)
This quantitative study was conducted to find out the relationship between Foreign Language Anxiety (FLA) and the achievements of non-English major university students in Indonesia. Through descriptive analysis, the study found that learners experienced various degrees of FLA with the mean score 93.07 (SD = 17.69, N = 119). This study also found a statistically significant, negative correlation between the learners’ FLA and their achievements as measured with their grades, r (117) = -.37, p < .01. Consistent with that, significant, negative relationships were also found between the learners' achievements and all the three related situation-specific anxieties, namely, communication apprehension, test anxiety, and fear of negative evaluation. Considering the results, it is suggested that both teachers and students should minimise the debilitating effects of students’ FLA. Based on the limitations of this study, some recommendations for future researches are also stated. Suggested directions of future researches on FLA in Indonesia are investigations on the relationship between FLA and achievements across different levels of education as well as thorough qualitative investigations of FLA. Keywords: Foreign Language Anxiety, learners’ achievements, correlations.